PEMETAAN KEMANDIRIAN KEUANGAN DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - B61112028, NUR AHMAD PRAMUDI (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT Â The research entitled â€œThe Maping Local Financial Independence and Economic Growth of Regencies/Cities in West Kalimantan Provinceâ€ aimed to know and analyse level of Local Financial Independence in every regency/city and make typology between local financial independence (local financial ratio) and economic growth of regencies/cities in West Kalimantan province by using typology classment, and known influence of local fianancial (local financial ratio) to economics growth of regencies/cities in West Kalimantan. Research findings showed that the level of local financial independence in every regency/city in West Kalimantan province varied at approximately 4,36% and average of economic growth was 5,10. The result of regresion analisis showed that the local financial (Local Financial Independence Ratio) influented to economics growth is not significant. The result of according to the typology of local financial independence and economic growth, shown/known that a region that placed in 1stQuadran (Developed/first level) is Pontianak City, Singkawang City, and Sekadau Regency. The region that placed on 2nd Quadran (developed/second level) is Landak regency, Ketapang,Â Sambas, Sintang, and Kubu Raya regency. The placed that potensial (3thQuadran is Mempawah regency, and the region that placed 4th Quadran (Underdeveloped) is Kayong UtaraÂ regency, Bengkayang, Kapuas Hulu, Sanggau and Melawi regency. Keywords : Local Income (Revenue), Local Financial Independence Ratio, Economic Growth.Â